Pengaruh Pupuk Kasgot Hasil Biokonversi Limbah Kulit Lada Putih Menggunakan Lalat Tentara Hitam Terhadap Pertumbuhan Tanaman Tomat Rampai (Lycopersicon Pimpinellifolium) - Hani Hidayah; Ida Kinasih; Ramadhani Eka Putra (Lembaga Pengembangan Kinerja Dosen, 2023)
Utilizing white pepper peel waste (Pipper nigrum L.) as compost can minimize the problem of pepper peel waste. This research uses black soldier flies (BSF), the results of which are maggots as fertilizer for the growth of potpourri tomato plants (Lycopersicon pimpinellifolium). The aim of this research is to determine the quality of compost from white pepper skin waste resulting from bioconversion using BSF, and its effect on the growth of potpourri tomato plants. This research used an experimental method by pre-fermenting white pepper skin waste using 50 ml EM4 for 2, 3, 4 weeks and then using it as food for BSF larvae. Next, the cassava results are applied to potpourri tomato plants with P1 (1 kg of soil: 5 kg of cassava 2 weeks), P2 (1 kg of soil: 5 kg of cassava 3 weeks), P3 (1 soil: 5 kg of cassava 4 weeks), P4 (1 kg : 10 kg cashgot 2 weeks), P5 (1 kg : 10 kg cashgot 3 weeks), P6 (1 kg : 10 kg cashgot 4 weeks) and control (soil without cashgot). The data were analyzed using ANOVA via the SPSS 26 application. The cassava application showed that there was a significant effect on the highest plant height P6 (22.98 inches), the highest stem diameter P1 (4.58 mm), the highest number of leaves P3 (108.67 leaves), the highest fruit diameter was P2 (17.97) and the highest fruiting time was P0 (29.75). The highest number of fruit is P1 (13 fruits/plant), the highest fruit weight is P5 (39 grams/plant). In conclusion, P1 treatment is the best quality compost for the growth of potpourri tomatoes which is thought to have N (0.22%), P (0.15%), K (0.01%), C-organic (5.84) and a C/ N (26.5).